The Kharijites in Early Islamic Historical Tradition: Heroes and Villains - Hagemann, Hannah-Lena (Edinburgh Studies in Classical Islamic History and Culture Ser., 2021)
Analyses the narrative function of Khārijism in 9th- and 10th-century Islamic historiography.